Advanced Study of Promoted Pt /SAPO-11 Catalyst for Hydroisomerization of the n-Decane Model and Lube Oil - Aljendeel, Haider; Hussein, Hussein Qasim (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
SAPO-11 is synthesized from silicoaluminophosphate in the presence of di-n-propylamine as a template. The results show that the sample obtained has good crystallinity, 396m2/g BET surface area, and 0.35 cm3/g pore volume. The hydroisomerization activity of (0.25)Pt (1)Zr (0.5)W/SAPO-11 catalyst was determined using n-decane and base oil. All hydroisomerization experiments of n-decane were achieved at a fixed bed plug flow reactor at a temperature range of 200-275°C and  LHSV 0.5-2h-1.  The results show that the n-decane conversion increases with increasing temperature and decreasing LHSV, the maximum conversion of 66.7 % was achieved at temperature 275°C and LHSV of 0.5 h-1. Meanwhile, the same catalyst was used to improve base oil specification by increasing viscosity index and decreasing pour point. The isomerization reaction conditions, employed are temperature (200-300)ºC, the liquid hourly space velocity of 0.5-2h-1, and the pressure kept atmospheric. The present study shows that Pt Zr W/SAPO-11 minimizes the pour point of lubricating oil to -16°C at isomerization temperature of  300°C and LHSV of 0.5 h-1 and viscosity index 134.8.